1995
DOI: 10.1002/j.2161-0045.1995.tb00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Female Students Who Aspire to Science and Engineering or Homemaking Occupations

Abstract: This study identified predictors that discriminated between nontraditional and traditional career aspirations in a sample composed of 930 eighth‐grade female students (52 Asian Americans, 123 Hispanics, 61 African Americans, 669 Whites, and 15 Native Americans). Results indicated that the students who aspired to careers in science or engineering scored significantly higher on educational aspirations; perceived parental expectations; student‐reported grade point averages (GPAs); and mathematics, reading, and sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 31 publications
4
40
1
Order By: Relevance
“…Consistent with findings from other studies (Mau,[12], [13]; Mau, Domnick, & Ellsworth, [14]), we found female and minority students, except for Asian American students, were less likely than male or White students to declare a STEM major. Similarly, among those who completed a STEM major, a smaller percentage of female and minority students completed their degree in 5 years than their counterparts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with findings from other studies (Mau,[12], [13]; Mau, Domnick, & Ellsworth, [14]), we found female and minority students, except for Asian American students, were less likely than male or White students to declare a STEM major. Similarly, among those who completed a STEM major, a smaller percentage of female and minority students completed their degree in 5 years than their counterparts.…”
Section: Discussionsupporting
confidence: 92%
“…Of 2,453 CIP majors listed, 498 majors (20%) were classified as STEM majors that involve Science (CIP code 40), Technology (CIP code 11), Engineering (CIP code 14), and Mathematics (CIP code 27). The persistence dependent variable use for research question 3 is defined in the analysis section.…”
Section: Methodsmentioning
confidence: 99%
“…It is interesting that academic performance has been identified as an important predictor from previous studies (e.g., Mau, 2003;Mau, Domnick, & Ellsworth, 1995) but was found to have minimal predictive power in this study. We believe that students' academic proficiency may only influence persistence in certain career pursuits, such as science or engineering-related careers.…”
Section: Discussionmentioning
confidence: 89%
“…Although males had higher science-and math-related scores, women outperformed men in tests of writing ability. Differences in career aspirations-toward science/engineering careers vs. homemaker-were found in five racial-ethnic subgroups of American female eighth graders (Mau, Domnick, & Ellsworth, 1995). A study of female undergraduate home economics majors showed important differences in personality indices when correlated with choice of subspecialty.…”
Section: Gendermentioning
confidence: 95%